The Role of Vehicular Cloud Computing in Road Traffic Management: A Survey - Ahmad, I.; Noor, Rafidah Md; Ali, I.; Qureshi, M.A. (Springer Verlag, 2017)
The vehicular cloud computing (VCC) is an emerging technology that changed the vehicular communication and underlying traffic management applications. The underutilized resources of vehicles can be shared with other vehicles over the VANET to manage the road traffic more efficiently. The cloud computing and its capability of integrating and sharing resources, plays potential role in the development of traffic management systems (TMSs). This paper reviews the VCC based traffic management solutions to analyze the role of VCC in road traffic management. Particularly, an analysis of VANET based and VCC based TMSs is presented. To explore, the VANET infrastructure and services, a comparison of VCC based TMSs is provided. A taxonomy of vehicular clouds is presented, in order to identify and differentiate the type of vehicular cloud’s integration. Potential future challenges and their solutions in respect of emerging technologies are also discussed. The VCC is envision to play an important role in further development of intelligence transportation system.